Nilai Pendidikan Karakter Perspektif Az-Zarnuji Dalam Kitab Ta'lim Al-Muta'allim - Nada Nabilah; Muhammad Mustofa; Nailin Najihah (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2022)
This research departs from Az-Zarnuji's assumption regarding the number of students who have actually tried seriously the tut menu of knowledge but they cannot feel the joy of knowledge due to lack of attention or even abandoning morals in the process of studying. In his book, Az-Zarnuji also offers an educational concept that focuses on learning by doing which refers to ethnically oriented. This research is a library study research or also called library research. The method used is descriptive analysis, which only describes what it is about variables, symptoms, or circumstances. Data sources used as support in this study include books, journals, and other supporting sources. From the research above, it produces some of the values of character education in the book of Ta'lim Al-Muta'alliim such as the attitude of always being deliberative, the attitude of always being patient and steadfast in studying, the attitude of always keeping oneself from something. It can be concluded, The main student character is a character based on tauhid values ​​which is the basis and goal of every learner's behavior.